From surveillance to pathogenesis: characterization of genotype V of chicken infectious anemia virus - Su, Zetao; Leng, Mei; Wu, Zhiqiang; Chen, Wenjing; Yang, Shenghua; Li, Xuesong; Huo, Guanming; Yin, Lijuan; Qin, Jianping; Lin, Wencheng (Frontiers in Veterinary Science, 2025)
IntroductionChicken infectious anemia virus (CIAV) is a globally distributed immunosuppressive pathogen that causes substantial economic losses in the poultry industry.MethodsFrom 2023 to 2024, 408 clinical samples were collected from diseased chickens to investigate the molecular epidemiology and genetic diversity of CIAV strains circulating in southern China. A representative genotype V strain WSFL24 was further characterized by complete genome sequencing and pathogenicity evaluation using specific-pathogen-free (SPF) chicks.ResultsAmong the collected samples, 153 (37.5%) tested positive for CIAV. A total of 21 CIAV isolates were isolated and classified the isolates into genotype IIIa (13 isolates) and V (8 isolates). The genotype V strain WSFL24 possessed 31 amino acid substitutions in VP1, including virulence-associated residues (Q139, Q144, and Q394). Moreover, WSFL24 caused 60% mortality, severe anemia (hematocrit <27%), pronounced thymic atrophy, elevated viral loads in lymphoid tissues and cloacal swabs, and distinct histopathological lesions compared with the attenuated reference strain Cux-1 (genotype IIIb).DiscussionThese results demonstrate the emergence and enhanced virulence of genotype V CIAV strains in southern China. The findings emphasize the need for continuous molecular surveillance and the development of updated vaccines to control evolving virulent genotypes.